Conidia of the insect pathogenic fungus, Metarhizium anisopliae, fail to adhere to mosquito larval cuticle. Issue 2 (October 2014) - Greenfield, Bethany P. J.; Lord, Alex M.; Dudley, Ed; Butt, Tariq M.
Abstract : Adhesion of conidia of the insect pathogenic fungus, Metarhizium anisopliae, to the arthropod host cuticle initially involves hydrophobic forces followed by consolidation facilitated by the action of extracellular enzymes and secretion of mucilage. Gene expression analysis and atomic force microscopy were used to directly quantify recognition and adhesion between single conidia of M. anisopliae and the cuticle of the aquatic larval stage of Aedes aegypti and a representative terrestrial host, Tenebrio molitor . Gene expression data indicated recognition by the pathogen of both hosts; however, the forces for adhesion to the mosquito were approximately five times lower than those observed for Tenebrio . Although weak forces were recorded in response to Aedes, Metarhizium was unable to consolidate firm attachment. An analysis of the cuticular composition revealed an absence of long-chain hydrocarbons in Aedes larvae which are thought to be required for fungal development on host cuticle. This study provides, to our knowledge, the first evidence that Metarhizium does not form firm attachment to Ae. aegypti larvae in situ, therefore preventing the normal route of invasion and pathogenesis from occuring.